Low-level control algorithms for manipulator with variable number of links - Romanova, I. K.; Chernyshov, N. M. (AIP conference proceedings, 2022)
Various types of manipulators are used in a wide spectrum of industries, and they found their application in solving many problems ranging from civilian to military. This gave rise to a large number of different modifications of robots of this type and, as a consequence, not lesser number of systems engineering and algorithmic solutions. Alteration in the robot operating conditions inevitably leads to the need of transferring the production line to machines different from those used. Manipulator with variable number of links considered in this article was designed and developed for multifunctional use. Each link of such a manipulator is unified, which allows user to quickly change the design for a wide range of tasks. Moreover, special qualification of the assembler is not required. However, it is also necessary to ensure uniformity of the automatic control system algorithms for each separate link to provide complete flexibility in using such a device in addition to unification in the design. As a solution to this problem, an algorithm is proposed that is described for a microprocessor system that controls each separate manipulator module. According to the stated conditions, position of each device module is algorithmically determined in the general automatic control system. Based on this information, as well as on data received from the sensors, the control signal shape is formed. Thus, the program code processed by the module microprocessor systems is identical for each link of the manipulator. Presented article considers theoretical and practical aspects of the low-level unified algorithm. Solution to this problem is proposed, and analysis of the algorithm positive features and disadvantages is carried out.